Diagnosis and Management of Vaccine-Related Thrombosis following AstraZeneca COVID-19 Vaccination: Guidance Statement from the GTH - Oldenburg, Johannes; Klamroth, Robert; Langer, Florian; Albisetti, Manuela; von Auer, Charis; Ay, Cihan; Korte, Wolfgang; Scharf, Rüdiger E.; Pötzsch, Bernd; Greinacher, Andreas (Hämostaseologie, 2021)
The COVID-19 pandemic is an ongoing global healthcare crisis. Based on reports of atypically located thromboses following vaccination with the AstraZeneca COVID-19 vaccine, the Society of Thrombosis and Haemostasis Research (GTH) has issued guidance statements on the recognition, diagnosis, and treatment of this rare complication. It shares pathophysiological features with heparin-induced thrombocytopenia (HIT) and is referred to as vaccine-induced prothrombotic immune thrombocytopenia (VIPIT).
Keywords: platelet antigens; thrombosis; SARS-CoV-2; vaccine